Influence of range, angle of view, image resolution and image compression on underwater stereo-video measurements: High-definition and broadcast-resolution video cameras compared - Harvey, Euan; Goetze, J.; McLaren, B.; Langlois, T. (Marine Technology Society, 2010)
An investigation of how increasing the distance and angle to objects of interest affected the measurement accuracy and precision achievable with high-definition and medium-resolution PAL stereo-video systems was conducted. A test was also conducted to determine whether varying the compression of the imagery influenced measurement accuracy and precision. Measurements of five different lengths of PVC pipe (ranging from 51.5 to 3,001 mm) that represented the lengths of reef fishes routinely sampled with stereo-video were made at 1 m intervals out to the maximum visibility (9 m range) over three different angles (90°, 80° and 70°). High-definition stereo-video imagery was compressed at three different bit-rates. The results show that higher definition stereo-video imagery allows objects to be measured more accurately and precisely over greater ranges. When both ends of a target can be clearly seen in high-definition stereo-video imagery, the associated error is approximately 1% of the total length of the object. There was no deleterious effect on accuracy or precision from increasing the angle of view. Lower compression did not result in more accurate and precise length estimates. The configuration of a stereo-video system needs to match the task of a particular survey, as changes in the base separation and angle of convergence will affect the accuracy and precision of measurements. With full high-definition systems, smaller lengths (<50 mm) of PVC could not be accurately measured at distances greater than 5 m whereas longer lengths (500-3,001 mm) could be measured with acceptable accuracy and precision at 9 m.